Accuracy and calibration of integrated radiation output indicators in diagnostic radiology: A report of the AAPM Imaging Physics Committee Task Group 190. Issue 12 (6th November 2015) - Lin, Pei‐Jan P.; Schueler, Beth A.; Balter, Stephen; Strauss, Keith J.; Wunderle, Kevin A.; LaFrance, M. Terry; Kim, Don‐Soo; Behrman, Richard H.; Shepard, S. Jeff; Bercha, Ishtiaq H.
Abstract : Due to the proliferation of disciplines employing fluoroscopy as their primary imaging tool and the prolonged extensive use of fluoroscopy in interventional and cardiovascular angiography procedures, "dose‐area‐product" (DAP) meters were installed to monitor and record the radiation dose delivered to patients. In some cases, the radiation dose or the output value is calculated, rather than measured, using the pertinent radiological parameters and geometrical information. The AAPM Task Group 190 (TG‐190) was established to evaluate the accuracy of the DAP meter in 2008. Since then, the term "DAP‐meter" has been revised to air kerma‐area product (KAP) meter. The charge of TG 190 (Accuracy and Calibration of Integrated Radiation Output Indicators in Diagnostic Radiology) has also been realigned to investigate the "Accuracy and Calibration of Integrated Radiation Output Indicators" which is reflected in the title of the task group, to include situations where the KAP may be acquired with or without the presence of a physical "meter." To accomplish this goal, validation test protocols were developed to compare the displayed radiation output value to an external measurement. These test protocols were applied to a number of clinical systems to collect information on the accuracy of dose display values in the field.